2004
DOI: 10.1080/16501960410023877
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues and research recommendations for mild traumatic brain injury: the who collaborating centre task force on mild traumatic brain injury

Abstract: The WHO Collaborating Centre for Neurotrauma Task Force on Mild Traumatic Brain Injury performed a comprehensive search and critical review of the literature published between 1980 and 2002 to assemble the best evidence on the epidemiology, diagnosis, prognosis and treatment of mild traumatic brain injury. Of 743 relevant studies, 313 were accepted on scientific merit and comprise our best-evidence synthesis. The current literature on mild traumatic brain injury is of variable quality and we report the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
583
1
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 859 publications
(598 citation statements)
references
References 291 publications
2
583
1
12
Order By: Relevance
“…In such a group it would be reasonable that additional data could be obtained that would provide more information about the biomechanics of injury and a host of other medical and demographic factors, including attempts to be establish preinjury level of function. In one of the largest reviews of mTBI, the WHO task force that reviewed mTBI literature up to 2004 concluded that mTBI research is "of varying quality and causal inferences are often mistakenly drawn from cross-sectional studies (p. 84," (Carroll et al, 2004a), see also (Ragnarsson, 2006) The only correction for this gaffe in the neuropsychology of concussion, and potential long-term sequelae of PPCS, will be large, unbiased prospective studies that address the issues raised in this review. The importance of understanding this more accurately and completely is the fact that concussion is reportedly the most common of all neurological injuries and this is also true of the Iraq and Afghanistan war (Das & Moorthi, 2005;Okie, 2005;Warden, 2006;Warden & French, 2005), where unofficial estimates place the numbers in the tens of thousands (Bob Woodruff Reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such a group it would be reasonable that additional data could be obtained that would provide more information about the biomechanics of injury and a host of other medical and demographic factors, including attempts to be establish preinjury level of function. In one of the largest reviews of mTBI, the WHO task force that reviewed mTBI literature up to 2004 concluded that mTBI research is "of varying quality and causal inferences are often mistakenly drawn from cross-sectional studies (p. 84," (Carroll et al, 2004a), see also (Ragnarsson, 2006) The only correction for this gaffe in the neuropsychology of concussion, and potential long-term sequelae of PPCS, will be large, unbiased prospective studies that address the issues raised in this review. The importance of understanding this more accurately and completely is the fact that concussion is reportedly the most common of all neurological injuries and this is also true of the Iraq and Afghanistan war (Das & Moorthi, 2005;Okie, 2005;Warden, 2006;Warden & French, 2005), where unofficial estimates place the numbers in the tens of thousands (Bob Woodruff Reports.…”
Section: Resultsmentioning
confidence: 99%
“…systemic injuries, facial injuries or intubation), caused by other problems (e.g., psychological trauma, language barrier or coexisting medical conditions) or caused by penetrating craniocerebral injury, p. 115). (Carroll et al, 2004a) of what is now currently known about the neuropathological and pathophysiological basis of concussion will be offered. The last part of the review will focus on more traditional neuropsychological concepts as they relate to concussion and conclude with suggestions on improved research tactics on this topic.…”
Section: European Federation Of Neurological Societies -2002 Task Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Mild TBI, synonymous with concussion, is the most frequently occurring category, comprising approximately 85 percent of all TBI episodes [3]. Mild TBI has been clinically operationalized as a nonpenetrating force to the head that results in (1) confusion or disorientation, LOC for 30 min or less, posttraumatic amnesia for less than 24 h, and/or other transient neurological abnormalities such as focal signs, seizure, and intracranial lesion not requiring surgery; and (2) a Glasgow Coma Scale score of 13 to 15 after 30 min postinjury or later upon presentation for healthcare [4]. TBI of all severity levels can cause substantial long-term functional disability among survivors [1].…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…14,15 Mild TBI was further subdivided into 3 categories: mild I (no abnormalities on computed tomography [CT] or no CT was performed); mild II (skull fracture without intracranial hemorrhage); and mild III (intracranial hemorrhage but case still meet criteria for mild TBI).…”
Section: Definition Of Injuriesmentioning
confidence: 99%